By crumbs, it's mine! - Beatty, Patricia (New York : William Morrow and Company, Inc., 1976)
While stranded in the Arizona territory in the 1880's a thirteen-year-old girl finds herself the owner of a traveling hotel.
1. My elephant -- 2. Leacock -- 3. Boyd valley -- 4. Little old jess -- 5. Some surprise! -- 6. "Up she goes!" -- 7. A message from the interior -- 8. We make some progress -- 9. Enough! -- 10. Changes -- 11. More than enough -- 12. Showdown!.
Keywords: TEENAGE GIRLS -- JUVENILE-FICTION -- HUMOROUS STORIES